Spatial Characteristics and Dynamics of Provincial Total Factor Productivity in China. - Zhu, S; Lai, M; Fu, X (Taylor and Francis, 2008)
This paper explores the influence of spatial effects on the convergence of total factor productivity (TFP) across Chinese regions. We use the Moran index, Markov transition matrix and panel data techniques to analyse spatial dependence, transition dynamics and disparities in TFP across Chinese provinces over the period from 1978 to 2004. We find that in the period following 1978, there has been an increase in spatial dependence in provincial-level TFPs across the various regions in China. However, the extent of this dependence is not the same across regions and the direction of movement of provincial TFP does not show convergence. On the contrary, provincial TFPs at the middle quintile level moved to the quintile levels at the highest and lowest levels, suggesting divergence and polarization in TFP across Chinese regions. The ‘New Eastern Region’ appears to be a TFP convergence club over the sampling period but no evidence is found suggesting convergence of TFP between provinces in the other subgroups. Policy implications are discussed.